Sprawność fizyczna warszawskiej młodzieży gimnazjalnej - Joanna Nieczuja-Dwojacka (Studia Ecologiae et Bioethicae, 2015)
The aim of project was to estimate relationship between physical activity, socio-economic conditions and BMI in sample of youth. A group consisted of 177 youth aged 14-16 years from two Warsaw junior high schools. The research included questionnaire information (socio-economic condition, lifestyle), measurements and tests of strength, agility, endurance, flexibility, and reaction time. To determinate the relationship between fitness and five factors stepwise multiple regression was used. The results showed that higher stress level had negative influence on grip strength of hand and agility of shuttle run. Exposure to smoking had a negative impact on result in grip strength of hand, endurance, and explosive power of the lower extremities. The number of people in family had negative effect on grip strength of hand, however lifestyle had a positive influence on number of sit-ups (abdominal muscular strength and endurance). In case of youth characterized by lower BMI category, weaker handgrip and increased spine flexibility were observed. Socio-economic conditions mentioned above had small influence on physical activity